Prevalence of H. pylori in Immune Thrombocytopenic Purpura (ITP) in a tertiary care center, South India - Antony, Anny; Dr. C. Margaret; Karthick, R.; Ali, Mohammed; Chenthil, K.S. (International Journal of Medical Research and Review, 2019)
Introduction: Immune thrombocytopenic purpura (ITP) has been linked with Helicobacter Pylori infection. Objectives: The objective of the present study was to determine the prevalence of H pylori infection in adult ITP patients in a tertiary care center in South India. Methods: 50 adult patients with ITP in the Department Hematology, Madras Medical College were recruited for a cross -sectional study over a period of 6 months. Biopsy from the antrum was subjected to Rapid urease test to detect H. pylori. A total of 50 patients participated in the study. Result: The prevalence of H. pylori infection in ITP patients was 36%. The majority of patients were male (78%). Conclusion: The diagnosis of H. pylori in ITP patients may be considered in high prevalent areas.